Evaluation of the synergistic effect of cinnamon extract and honey against multidrug-resistant isolates of Pseudomonas aeruginosa recovered from burn unit. Issue 2 (April 2020) - Karami, Pezhman; Khaledi, Azad; Dastan, Dara; Yaghoobi, Mojtaba Hedayat; Karami, Manoochehr; Mashoof, Rasool Yousefi; Alikhani, Mohammad Yousef
Abstract : Background: Due to rapid increase of drug resistance and failure of the current antibiotics to treat infections caused by Pseudomonas aeruginosa multidrug-resistant (MDR) isolates, introduction of the new therapeutic combinations is needed. This study aimed to evaluate the synergistic effects of cinnamon extracts and honey against MDR isolates of P. aeruginosa recovered from burn unit. Methods: The minimum inhibitory concentration (MIC) and minimum bactericidal concentrations (MBC) of each antibiotic (Gentamicin and Ciprofloxacin) alone or in combination with the aqueous and alcoholic extracts of cinnamon and honey was determined by broth microdilution method for clinical and environmental isolates of P. aeruginosa based on the Clinical & Laboratory Standards Institute ( CLSI ) guidelines. The synergistic effect of combinations was evaluated using a checkerboard test. Data analyzed using chi-square and Fisher's exact tests (SPSS software). P -value of less than 0.05 was considered to indicate statistically significant differences. Results: The mean MICs for Cinnamomum zeylanicum alcoholic extract-honey(CZAH), C. zeylanicum watery extract–honey(CZWH), Ciprofloxacin– C. zeylanicum watery extract (CPCZW), Gentamicin– C. zeylanicum watery extract (GMCZW), Ciprofloxacin— C. zeylanicum alcoholic extract (CPCZA), Gentamicin– C. zeylanicum alcoholic extract (GMCZA), Ciprofloxacin—honey (CPH), Gentamicin–honey (GMH) against MDR strains were as 6.80, 15.63, 18.62, 5.84, 10.70, 3.84 and 36.88 μg/ml, respectively. The mean MBC for CZAH, CZWH, CPCZW, GMCZW, CPCZA, GMCZA, CPH and GMH against MDR strains were as 13.17, 30.25, 29.63, 31.52, 11.32, 21.28, 60.11 and 70.03 μg/ml, respectively. According to the FICi results, 14.1, 1.3, 3.8, 19.2, 32.1, 29.5, 9 and 9% of isolates had the synergism for CZAH, CZWH, CPCZW, GMCZW, CPCAA, GMCZA, CPH and GMH combinations, respectively. Conclusion: This study showed a proper synergistic effect of aqueous and alcoholic extracts of cinnamon and honey in combination with Ciprofloxacin and Gentamicin against MDR isolates of P. aeruginosa .